Pengaruh Layanan Bantuan dan Keamanan Transaksi terhadap Pengalaman Emosional Pengguna dengan Kepuasan Pelanggan sebagai Mediator - Lafreda Nanda Wibowo; Widarto Rachbini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effect of Assistance Services and Transaction Security on User Emotional Experience, with Customer Satisfaction as a mediating variable in the context of using a digital wallet (e-wallet). This study uses a quantitative approach with a causal-comparative method. Data collection was carried out by distributing online questionnaires using Google Form to 150 respondents who are active e-wallet users. The research model consists of four latent variables, each of which is measured by three reflective indicators. The data analysis technique uses the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS software, and is supported by descriptive analysis using SPSS. Validity and reliability tests are carried out through outer loading tests, Average Variance Extracted (AVE), Cronbach's Alpha, and Composite Reliability. Hypothesis testing is carried out by considering the path coefficient, t-statistic, and p-value values. The results of the study indicate that Assistance Services and Transaction Security have a significant effect on Customer Satisfaction. Assistance Services also have a direct effect on Emotional Experience, while Transaction Security does not have a direct effect on this variable. Customer Satisfaction has a significant effect on Emotional Experience, and is proven to be a significant mediator in the relationship between Assistance Service and Transaction Security on Emotional Experience.